Biological Function of Long Non-coding RNA (LncRNA) Xist - Wang, Wenlun; Min, Lu; Qiu, Xinyuan; Wu, Xiaomin; Liu, Chuanyang; Ma, Jiaxin; Zhang, Dongyi; Zhu, Lingyun (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) regulate gene expression in a variety of ways at epigenetic, chromatin remodeling, transcriptional, and translational levels. Accumulating evidence suggests that lncRNA X-inactive specific transcript (lncRNA Xist) serves as an important regulator of cell growth and development. Despites its original roles in X-chromosome dosage compensation, lncRNA Xist also participates in the development of tumor and other human diseases by functioning as a competing endogenous RNA (ceRNA). In this review, we comprehensively summarized recent progress in understanding the cellular functions of lncRNA Xist in mammalian cells and discussed current knowledge regarding the ceRNA network of lncRNA Xist in various diseases. Long non-coding RNAs (lncRNAs) are transcripts that are more than 200 nt in length and without an apparent protein-coding capacity (Furlan and Rougeulle, 2016; Maduro et al., 2016). These RNAs are believed to be transcribed by the approximately 98–99% non-coding regions of the human genome (Derrien et al., 2012; Fu, 2014; Montalbano et al., 2017; Slack and Chinnaiyan, 2019), as well as a large variety of genomic regions, such as exonic, tronic, and intergenic regions. Hence, lncRNAs are also divided into eight categories: Intergenic lncRNAs, Intronic lncRNAs, Enhancer lncRNAs, Promoter lncRNAs, Natural antisense/sense lncRNAs, Small nucleolar RNA-ended lncRNAs (sno-lncRNAs), Bidirectional lncRNAs, and non-poly(A) lncRNAs (Ma et al., 2013; Devaux et al., 2015; St Laurent et al., 2015; Chen, 2016; Quinn and Chang, 2016; Richard and Eichhorn, 2018; Connerty et al., 2020). A range of evidence has suggested that lncRNAs function as key regulators in crucial cellular functions, including proliferation, differentiation, apoptosis, migration, and invasion, by regulating the expression level of target genes via epigenomic, transcriptional, or post-transcriptional approaches (Cao et al., 2018). Moreover, lncRNAs detected in body fluids were also believed to serve as potential biomarkers for the diagnosis, prognosis, and monitoring of disease progression, and act as novel and potential drug targets for therapeutic exploitation in human disease (Jiang W. et al., 2018; Zhou et al., 2019a). Long non-coding RNA X-inactive specific transcript (lncRNA Xist) are a set of 15,000–20,000 nt sequences localized in the X chromosome inactivation center (XIC) of chromosome Xq13.2 (Brown et al., 1992; Debrand et al., 1998; Kay, 1998; Lee et al., 2013; da Rocha and Heard, 2017; Yang Z. et al., 2018; Brockdorff, 2019). Previous studies have indicated that lncRNA Xist regulate X chromosome inactivation (XCI), resulting in the inheritable silencing of one of the X-chromosomes during female cell development. Also, it serves a vital regulatory function in the whole spectrum of human disease (notably cancer) and can be used as a novel diagnostic and prognostic biomarker and as a potential therapeutic target for human disease in the clinic (Liu et al., 2018b; Deng et al., 2019; Dinescu et al., 2019; Mutzel and Schulz, 2020; Patrat et al., 2020; Wang et al., 2020a). In particular, lncRNA Xist have been demonstrated to be involved in the development of multiple types of tumors including brain tumor, Leukemia, lung cancer, breast cancer, and liver cancer, with the prominent examples outlined in Table 1. It was also believed that lncRNA Xist (Chaligne and Heard, 2014; Yang Z. et al., 2018) contributed to other diseases, such as pulmonary fibrosis, inflammation, neuropathic pain, cardiomyocyte hypertrophy, and osteoarthritis chondrocytes, and more specific details can be found in Table 2. This review summarizes the current knowledge on the regulatory mechanisms of lncRNA Xist on both chromosome dosage compensation and pathogenesis (especially cancer) processes, with a focus on the regulatory network of lncRNA Xist in human disease.